Individual arousal-related performance zones effect on temporal and behavioral patterns in golf routines - van der Lei, H.; Tenenbaum, G.; Land, W. M. (Psychology of Sport and Exercise, 2016)
Aim: Consistency, both in duration and behavior, of pre-performance routines has been closely related to overall performance quality. However, recent findings highlight that psychological and physiological states may have important implications for routine consistency. To further clarify this relationship, the present study sought to examine changes in routine consistency with respect to optimal and non-optimal arousal states. Method: The present case study observed the performance routines of three high-skilled golfers during three rounds of competitive golf. Measures of arousal (heart rate) and outcome performance were used to determine each golfer`s Individual Arousal-related Performance Zones (IAPZs) (Kamata, Hanin, & Tenenbaum, 2002). Subsequently, temporal and behavioral patterns (consistency and number of rehearsal swings and glances toward the target) for both the full swing and golf putt were assessed across poor, moderate, and optimal levels of the golfer`s IAPZ. Results: Idiosyncratic differences in routine patterns, both behaviorally and temporally were evident. More importantly, the consistency of the routines for each golfer varied under different arousal-related performance zones. That is, the temporal and behavioral patterns of the golfers varied in idiosyncratic ways across the IAPZ levels. Conclusions: These findings suggest that factors that influence a performer`s arousal level can lead to idiosyncratic variations in a performer`s routine. Observation of these routine changes can provide insight into the negative tendencies that an athlete can have when performing outside their optimal zone. With this knowledge, practitioners can be more effective in helping athletes monitor and regulate arousal, which will ultimately lead to enhanced performance.